Neck Circumference: A Reliable Indicator of the Percent Body Fat in Young Male and Female Adults - Shyamal Koley, Davinder Kaur Dhillon (International Journal of Advanced Science and Technology, 2019)
Background: There are several methods which are being used for the assessment of body fat. The neck circumference measurement has recently become a new method of estimating the body fat. It is also used as an indicator of the body mass index. Several researchers have used this assessment method in their studies as a measure of estimating the adiposity and cardiovascular risk factors. The body mass index is a general indicator of the body weight and a rough indicator of fat-mass and fat-free mass. Whereas the percent body fat is the estimation of only the fat-mass in the body. The objective of the present study was to find out the association between the neck circumference and the percent body fat in order to find out if the neck circumference measurement is a reliable method of estimating the body fat. Materials and Methods: For the present study, normal healthy adult subjects with age group of 18-26 years were selected purposively from Amritsar, India. The sample size was 816 subjects which included 483 males and 333 females. The subjects underwent assessment for the neck circumference and percent body fat. For the body fat percentage calculation, measurements were taken for the triceps and subscapular skinfolds. From these measurements, percent body fat was calculated using gender specific formulas. Results: The results of inter-correlation matrix of the studied variables showed a significant (p<0.001) positive correlation of the neck circumference with percent body fat in both males and females. It was also observed that the males had significantly (p<0.001) higher mean values for the neck circumference than the females (38.43±2.62 cm and 32.81±2.15 cm respectively). However, the values of percent body fat were significantly (p<0.001) higher in females than in the males (21.53±6.42 % and 15.38±6.70 % respectively). Conclusion: The neck circumference can be considered as an important and reliable method of assessing the percent body fat which is a measure of health in young male and female adults.